In Vivo Evidence for a Prodrug Activation Mechanism during Colibactin Maturation. Issue 10 (6th June 2013) - Bian, Xiaoying; Fu, Jun; Plaza, Alberto; Herrmann, Jennifer; Pistorius, Dominik; Stewart, A. Francis; Zhang, Youming; Müller, Rolf
<x xml:space="preserve">Abstract</x> Releasing the cytopath: We have identified an N‐myristoyl‐D‐asparagine (1) as the free N‐terminal prodrug scaffold in cytopathogenic Escherichia coli strains expressing the colibactin gene cluster. Colibactin is released in vivo upon cleavage of precolibactin. We provide for the first time in vivo evidence of the prodrug‐like release mechanism of colibactin.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>